2018
DOI: 10.1021/acs.jafc.8b02772
|View full text |Cite
|
Sign up to set email alerts
|

Chemosensate-Induced Modulation of the Salivary Proteome and Metabolome Alters the Sensory Perception of Salt Taste and Odor-Active Thiols

Abstract: Oral stimulation with chemosensates was found to trigger changes in the composition of the salivary proteome and metabolome, which translate into a functional modulation of odor and taste perception. Orosensory intervention with 6-gingerol induced a significant increase in the abundance of salivary sulfhydryl oxidase 1, which was found to catalyze the oxidative decline of odor-active 2-furfurylthiol, thus resulting in a decrease in the odorant levels in exhaled breath, as shown by PTR-MS, and a reduction of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 51 publications
1
12
0
2
Order By: Relevance
“…On the contrary, Enberg and colleagues 39 showed the opposite results, with an increase in salivary TPC when studying the effect of acute alcohol consumption (0.7 g alcohol/kg of body weight for men and 0.6 g alcohol/kg of body weight for women). These results might reflect the stimulusspecificity of dietary taste compounds on the salivary proteome alteration, as previously indicated 16 .…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…On the contrary, Enberg and colleagues 39 showed the opposite results, with an increase in salivary TPC when studying the effect of acute alcohol consumption (0.7 g alcohol/kg of body weight for men and 0.6 g alcohol/kg of body weight for women). These results might reflect the stimulusspecificity of dietary taste compounds on the salivary proteome alteration, as previously indicated 16 .…”
Section: Discussionsupporting
confidence: 75%
“…Many of these studies have shown an impact on saliva composition after the chronic exposure of food or specific food ingredients. But, changes in salivary composition, such as in the salivary proteome, could be also produced immediately after the stimulation with tastant/chemesthetic compounds 16 . In this case, an immediate effect on salivary composition that in turn might affect the sensory perception of the food or beverage upon ingestion could be expected.…”
Section: Introductionmentioning
confidence: 99%
“…The metabolic composition of saliva is also influenced by stimulation and certain participant behaviors. Stimulation using citric acid caused a decrease in the majority of metabolites measured [90,91]. While this decrease is largely attributable to dilution due to increased fluid content of the saliva, metabolites were not diluted proportionally, indicating metabolite specific effects [91].…”
Section: Current Knowledge Of the Salivary Metabolomementioning
confidence: 94%
“…Following oral exposure to aspartame, salivary aspartate and phenylalanine concentrations (the constituent amino acids of aspartame) increased. Whether this is due to host or microbial peptidases is not clear [90].…”
Section: Role Of Host-microbiome Interactions In Modifying Salivary Mmentioning
confidence: 99%
“…Bader et al demonstrated the upregulation of lysozyme in saliva stimulated by citric acid rinse (41). The TRPV1 agonist 6-gingerol upregulated salivary sulfhydryl oxidase 1 resulting in reduced 2-furfurylthiol levels in exhaled breath and thus reduction in the perceived sulphur-like after-smell (42). However, the mechanism of these specific protein upregulations has not been elucidated.…”
Section: Introductionmentioning
confidence: 99%